2016
DOI: 10.1002/jnr.23741
|View full text |Cite
|
Sign up to set email alerts
|

The epileptic amygdala: Toward the development of a neural prosthesis by temporally coded electrical stimulation

Abstract: Many patients with epilepsy do not obtain proper control of their seizures through conventional treatment. We review aspects of the pathophysiology underlying epileptic phenomena, with a special interest in the role of the amygdala, stressing the importance of hypersynchronism in both ictogenesis and epileptogenesis. We then review experimental studies on electrical stimulation of mesiotemporal epileptogenic areas, the amygdala included, as a means to treat medically refractory epilepsy. Regular high-frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 205 publications
(251 reference statements)
0
27
0
5
Order By: Relevance
“…We speculate that the choice of coil type and stimulation area may be one of the reasons for the difference in study findings, and that the potential mechanism may be closely related to the amygdala. Recently, researchers have revealed that the amygdale pays a preponderant role in the pathogenesis of epilepsy (Cota et al, 2016). Although magnetic stimulation can cover the amygdala in our study, the circular coil has a disadvantage of poor targeting compared with a figure-of-eight coil.…”
Section: Discussionmentioning
confidence: 75%
“…We speculate that the choice of coil type and stimulation area may be one of the reasons for the difference in study findings, and that the potential mechanism may be closely related to the amygdala. Recently, researchers have revealed that the amygdale pays a preponderant role in the pathogenesis of epilepsy (Cota et al, 2016). Although magnetic stimulation can cover the amygdala in our study, the circular coil has a disadvantage of poor targeting compared with a figure-of-eight coil.…”
Section: Discussionmentioning
confidence: 75%
“…We opted to use a slower stimulation frequency to ensure that the neuronal circuits are not entrained, preventing eventual pro-ictal effects due to the stimulus [72] (for a review on the pro or anticonvulsant effects of various stimulation parameters, see Ref. [73]).…”
Section: Methodsmentioning
confidence: 99%
“…We opted to use a slower stimulation frequency to ensure that the neuronal circuits are not entrained, preventing eventual pro-ictal effects due to the stimulus [75] (for a review on the pro or anticonvulsant effects of various stimulation parameters, see Ref. [76]).…”
Section: Model Parameters and Modificationsmentioning
confidence: 99%